1978
DOI: 10.1056/nejm197811022991804
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Familial Medullary Thyroid Carcinoma

Abstract: To detect familial medullary thyroid carcinoma in a premetastatic stage, we administered tests provocative of calcitonin secretion (infusion of calcium or pentagastrin or both) each year for seven years to members of a pedigree now numbering 107. Since 1970, 21 patients converted from normal to abnormal secretory responses (two separate tests in which calcitonin levels exceeded 0.58 ng per milliliter). Twenty of 21 glands removed showed C-cell hyperplasia, and eight of the 20 also showed foci of carcinoma. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(42 citation statements)
references
References 17 publications
1
38
0
3
Order By: Relevance
“…The advent of sensitive calcitonin, catecholamine and parathyroid hormone assays and DNA-based screening programs changed the landscape for MEN2 (Graze et al 1978, Machens et al 2013a. Biochemical (i.e., calcitonin) screening was shown to be more sensitive than anatomical screening (i.e., neck ultrasonography) for microscopic disease (i.e., MTC) in asymptomatic children at risk of MEN2A (Morris et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of sensitive calcitonin, catecholamine and parathyroid hormone assays and DNA-based screening programs changed the landscape for MEN2 (Graze et al 1978, Machens et al 2013a. Biochemical (i.e., calcitonin) screening was shown to be more sensitive than anatomical screening (i.e., neck ultrasonography) for microscopic disease (i.e., MTC) in asymptomatic children at risk of MEN2A (Morris et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although a rising trend of calcitonin values may be sought as evidence of progressive tumour development, it should not necessarily be expected. Many investigators have reported fluctuation in levels between successive tests, even a normal result between two clearly abnormal ones (Graze et al 1978), presumably because of day-to-day variation in the calcitonin stores in the C-cells.…”
Section: Development Of Mtc In Familial Casesmentioning
confidence: 99%
“…On the face of it, therefore, the earlier the diagnosis is made, the better. (3) In centres where screening programmes were initiated several years ago, whereas the first round of screening yielded many family members with advanced disease, regular follow-up screening revealed individuals at the stage of C-cell hyperplasia or microscopic tumour (Graze et al 1978). Only prolonged follow up will prove that these screened individuals are in fact at very low risk of metastatic disease: it could be argued that there is a minority of individuals who have aggressive disease in whom the disease spreads early, and that screening, even at the earliest stage, may not be of benefit.…”
Section: Is Screening Of Benefit?mentioning
confidence: 99%
“…(Roman 2006, Wells 1994, Graze 1978. During the last decade, a great progress in the diagnostic identification of MTC has been made.…”
Section: Diagnosis Of Medullary Thyroid Carcinomamentioning
confidence: 99%